2007
DOI: 10.1016/j.cellsig.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential FAK phosphorylation at Ser-910, Ser-843 and Tyr-397 induced by angiotensin II, LPA and EGF in intestinal epithelial cells

Abstract: A rapid increase in the tyrosine phosphorylation of the non-receptor tyrosine kinase FAK is a prominent early event in fibroblasts stimulated by a variety of signaling molecules. However, a variety of epithelial cells, including intestinal epithelial cells, show a high basal level of tyrosine phosphorylated FAK that is only slightly further increased by addition of G protein-coupled receptors (GPCR) agonists or growth factors. In this study, we determined whether these stimuli could elicit FAK phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Recently, a large body of evidence suggested that a rapid increase of the tyrosine phosphorylation for a nonreceptor tyrosine kinase, FAK, is a common response to multiple GPCR agonists (Rozengurt, 2002). Interestingly, whereas /calmodulin-dependent protein kinase II (CaMKII), indicating that FAK is a point of integration of tyrosine and serine phosphorylation (Fan et al, 2005;Jacamo et al, 2007;Jiang et al, 2007). Our results showed that Ca 2ϩ signaling and FAK1 are involved in GABA B receptor-IGF-1R transactivation, suggesting that GABA B receptor-mediated Ca 2ϩ signaling may induce phosphorylation of FAK at Ser 843 , which in turn induces FAK tyrosine kinase activity and downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large body of evidence suggested that a rapid increase of the tyrosine phosphorylation for a nonreceptor tyrosine kinase, FAK, is a common response to multiple GPCR agonists (Rozengurt, 2002). Interestingly, whereas /calmodulin-dependent protein kinase II (CaMKII), indicating that FAK is a point of integration of tyrosine and serine phosphorylation (Fan et al, 2005;Jacamo et al, 2007;Jiang et al, 2007). Our results showed that Ca 2ϩ signaling and FAK1 are involved in GABA B receptor-IGF-1R transactivation, suggesting that GABA B receptor-mediated Ca 2ϩ signaling may induce phosphorylation of FAK at Ser 843 , which in turn induces FAK tyrosine kinase activity and downstream signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In CRC samples, the Ser-910-phosphorylated FAK was also elevated with development of tumor stages. Ser-843, the other serine residue of FAK, has also been reported to be phosphorylated in epithelial cells through a Ca 2+ -dependent manner (26). The elucidation of the precise role of FAK phosphorylation at Ser-843 in epithelial cells warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that EGF induces FAK phosphorylation at Ser-910 through an ERK-dependent pathway, inhibiting the ability of FAK to associate with paxillin and formation of focal adhesion complex (21,26). The reduced formation of focal adhesion contact is helpful for cell migration (20).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced Tyr 861 phosphorylation may be a direct structural consequence of altered conformational FAT dynamics and/or it may result indirectly from increased Tyr 925 phosphorylation, as the latter has been reported to influence Tyr 861 phosphorylation (50). FAK is also phosphorylated on several serine residues (44, 52) that regulate cell spreading and migration (53). The major such site in the C-terminal region of FAK is Ser 910 , a substrate of ERK (45).…”
Section: Discussionmentioning
confidence: 99%